Correction of Cytokine Imbalance in the Treatment of Stable Angina Pectoris - Khaydarova Zarrina Erkinovna; Khusainova Munira Alisherovna; Makhmudova Khanuza Davranovna; Khaydarov Sanjar Nizamitdinovich (Peerian Journals Publishing, 2022)
Coronary heart disease (CHD) is one of the most common causes of death in developed countries. This is due to the attention paid to the study of the pathogenesis of coronary heart disease. The main mechanisms leading to the development of acute coronary syndrome (ACS), unstable angina and acute myocardial infarction (AMI), are atherosclerosis and thrombosis. Despite the fact that atherosclerotic plaques narrowing the lumen of the coronary arteries cause inadequate myocardial perfusion and, consequently, the development of stable angina, ACS occurs only when these plaques are damaged and ruptured, followed by thrombosis. Many risk factors for the development and progression of coronary heart disease are known, but so far it has not been possible to fully explain what is the cause and trigger of acute coronary complications. Recently, the inflammatory theory of atherosclerosis has been widely discussed. The inflammatory theory of atherogenesis is confirmed by an increase in the concentration of markers of the inflammatory response in the blood of patients with coronary artery disease – C-reactive protein (CRP), neopterin, interleukin-6 (IL-6), fibrinogen, etc. Destabilization of the atherosclerotic plaque is determined by the high activity of the chronic inflammatory process. Neopterin is also a marker of activation of human cellular immunity. By its structure, neopterin is a condensed heterocyclic compound consisting of two parts – pyrimidine and pyrazine. Its main source is blood cells. IL-6 is a multifunctional cytokine and stimulates the proliferation of T-lymphocytes, macrophages, and endothelial cells. With the help of IL-6, endothelial cells, monocytes are activated and procoagulative reactions occur. Cytokines have a strong effect on the production of each other. In this network of mutual influences, almost all effects are stimulating, and only IL–6 suppresses the production of IL-1 and TNF-α. This feature of IL-6 determines its dual role in the development of inflammation: being a typical pro-inflammatory cytokine in its effects, it also has an anti-inflammatory effect.
Keywords: angina pectoris; TES therapy; cytokines; ACTH